2015
DOI: 10.3389/fpsyg.2015.01666
|View full text |Cite
|
Sign up to set email alerts
|

When deception becomes easy: the effects of task switching and goal neglect on the truth proportion effect

Abstract: Lying is typically more cognitively demanding than truth telling. Yet, recent cognitive models of lying propose that lying can be just as easy as truth telling, depending on contextual factors. In line with this idea, research has shown that the cognitive cost of deception decreases when people frequently respond deceptively, while it increases when people rarely respond deceptively (i.e., the truth proportion effect). In the present study, we investigated two possible underlying mechanisms of the truth propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…When instructed to lie versus tell the truth, we found that offenders made nearly twice as many errors and were substantially slower when lying compared to when telling the truth. This indicated that the behavioral costs of lying previously observed in undergraduate and community samples ([ 1 ], [ 3 ], [ 29 ]; [ 31 34 ]), generalizes to the forensic population (see [ 35 36 ]), and suggests that lying requires more mental effort than truth telling, also in offenders. According to the Activation-Decision-Construction-Action Theory (ADCAT; [ 37 ]), the cognitive cost of lying may be related to one or more of the following cognitive components: Automatic activation of the truth, the decision to lie, the construction of the lie, or acting sincere.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…When instructed to lie versus tell the truth, we found that offenders made nearly twice as many errors and were substantially slower when lying compared to when telling the truth. This indicated that the behavioral costs of lying previously observed in undergraduate and community samples ([ 1 ], [ 3 ], [ 29 ]; [ 31 34 ]), generalizes to the forensic population (see [ 35 36 ]), and suggests that lying requires more mental effort than truth telling, also in offenders. According to the Activation-Decision-Construction-Action Theory (ADCAT; [ 37 ]), the cognitive cost of lying may be related to one or more of the following cognitive components: Automatic activation of the truth, the decision to lie, the construction of the lie, or acting sincere.…”
Section: Discussionmentioning
confidence: 70%
“…This implies that aggregating cued and choice trials, there was a higher proportion of truth trials than lie trials for most participants. A higher proportion of truth trials may facilitate truthful responding and hamper deceptive responding ([ 29 ], [ 33 34 ]). The observation in the present study that a higher lying frequency on the choice trials was related to reduced lying difficulty, supports this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Answering a question with an honest response in half of the trials and with a dishonest response in the other half of trials precludes learning of a particular response to a question (see Foerster, Wirth, Herbort, Kunde, & Pfister, 2017). Indeed, increasing the frequency of dishonest responses to the inducer questions reduced the difference between honest and dishonest performance in probe questions (Van Bockstaele et al, 2012, 2015; Verschuere et al, 2011).…”
Section: Experiments 1: Transient and Sustained Adaptationmentioning
confidence: 97%
“…Such context effects have recently been reported in a range of studies that investigated how performance during lying and honest responding is affected by the recency and relative frequency of (dis)honest responding Foerster et al, 2016;Van Bockstaele et al, 2012;Van Bockstaele, Wilhelm, Meijer, Debey, & Verschuere, 2015;Verschuere, Spruyt, Meijer, & Otgaar, 2011). This broader perspective provides an elaborate approach to studying the role of cognitive control for dishonest responding by addressing dynamic changes in cognitive control (i.e., control adaptation).…”
mentioning
confidence: 87%
See 1 more Smart Citation